Public Trust, Ethic and Integrity in the Bureaucracy - Fauzi, Ahd; Sukaesih, Rita; Sauri, Sofyan; Handayani, Sri (PPSDP International Journal of Education, 2022)
It is critical to comprehend the requirement for a bureaucracy that is ethical, has integrity, and is devoid of corruption, collusion, and nepotism. This research seeks information on how public trust, ethics, and integrity in government exist in society. The technique employed in this study corresponds to descriptive analysis research principles, although in technical execution, this research is designed as an endeavor to interpret information rather than building or testing a hypothesis. According to the findings of this study, trust is extremely crucial for any institution or organization. To create and strengthen public faith in the government, including good will, leaders carry out their mandated tasks, leaders in their organizations follow all applicable rules, and government officials perform better.